Tratamento de epilepsia: consenso dos especialistas brasileiros Treatment of epilepsy: consensus of the Brazilian specialists - Luiz Eduardo Betting; Eliane Kobayashi; Maria Augusta Montenegro; Li Li Min; Fernando Cendes; Marilisa M. Guerreiro; Carlos A.M. Guerreiro (Arquivos de Neuro-Psiquiatria)
Epilepsia é uma condição muito freqüente em todo o mundo. Na última década, várias opções terapêuticas surgiram ou foram aprimoradas. O principal método utilizado para decisão terapêutica baseia-se nos estudos randomizados, que representam o maior nível de evidência. Entretanto, mesmo estes estudos são passíveis de críticas e em alguns casos o tratamento de escolha permanece controverso. Nestas situações, a opinião dos especialistas, na área da epileptologia, com maior experiência clínica, passa a ter grande valor. O presente estudo tem como principal objetivo elaborar um consenso de tratamento das epilepsias, através da opinião de experts brasileiros no assunto. Este consenso poderá auxiliar na criação de manuais e estratégias para o tratamento de determinadas síndromes epilépticas, de acordo com os padrões socioeconômicos brasileiros. Epilepsy is a frequent condition in the world. Recently a study in Brazil showed prevalence of 18/1000 inhabitants in São José do Rio Preto, São Paulo State. In the last decade, new therapeutic options were discovered or developed. The main therapeutic decision method is based on randomized clinical trials. This method represents the higher level of evidence. However, even these studies have limitations and in some cases the treatment of choice remains controversial. In these instances, the epilepsy experts' opinions become helpful. In 2001 a similar study had been conducted in USA. The aim of this study is to create guidelines for epilepsy treatment based on the opinion of the Brazilian experts. These guidelines can be used to create manuals and strategies for the treatment of some epileptic syndromes according to Brazilian experts. As compared to the North-American guidelines our study better reflects the resources available in our country.